Influence of different plant species on methane emissions from soil in a restored Swiss wetland. - Gurbir S Bhullar; Peter J Edwards; Harry Olde Venterink (PLoS ONE, 2014)
Plants are a major factor influencing methane emissions from wetlands, along with environmental parameters such as water table, temperature, pH, nutrients and soil carbon substrate. We conducted a field experiment to study how different plant species influence methane emissions from a wetland in Switzerland. The top 0.5 m of soil at this site had been removed five years earlier, leaving a substrate with very low methanogenic activity. We found a sixfold difference among plant species in their effect on methane emission rates: Molinia caerulea and Lysimachia vulgaris caused low emission rates, whereas Senecio paludosus, Carex flava, Juncus effusus and Typha latifolia caused relatively high rates. Centaurea jacea, Iris sibirica, and Carex davalliana caused intermediate rates. However, we found no effect of either plant biomass or plant functional groups--based on life form or productivity of the habitat--upon methane emission. Emissions were much lower than those usually reported in temperate wetlands, which we attribute to reduced concentrations of labile carbon following topsoil removal. Thus, unlike most wetland sites, methane production in this site was probably fuelled chiefly by root exudation from living plants and from root decay. We conclude that in most wetlands, where concentrations of labile carbon are much higher, these sources account for only a small proportion of the methane emitted. Our study confirms that plant species composition does influence methane emission from wetlands, and should be considered when developing measures to mitigate the greenhouse gas emissions.